2009
DOI: 10.1177/0022427809348898
|View full text |Cite
|
Sign up to set email alerts
|

Community Variations in Violence: The Role of Social Ties and Collective Efficacy in Comparative Context

Abstract: This article explores the relative roles of social ties and collective efficacy in explaining community variations in violent victimization in Australia. Using data from a survey of 2,859 residents across 82 communities in the city of Brisbane, coupled with official reported crime data provided by the Queensland Police Service and Australian Bureau of Statistics census data for 2001, the authors employ multilevel statistical models to depict the relative importance of social ties and collective efficacy in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 33 publications
6
117
3
2
Order By: Relevance
“…These findings suggest that it is possible to learn through community-based organisations how neighbourhood level changes can occur. Thus, developing strong institutional theories may be informative for developing strategies to reduce structural violence, rather than recording the density of community organisations in an area, a tendency found in other studies (Gardner and Brooks-Gunn 2009;Mazerolle et al 2010).…”
Section: Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings suggest that it is possible to learn through community-based organisations how neighbourhood level changes can occur. Thus, developing strong institutional theories may be informative for developing strategies to reduce structural violence, rather than recording the density of community organisations in an area, a tendency found in other studies (Gardner and Brooks-Gunn 2009;Mazerolle et al 2010).…”
Section: Future Directionsmentioning
confidence: 97%
“…Analyses of these processes have focussed on the differential ability of neighbourhoods to self-regulate and studies have found that collective efficacy, defined as 'the linkage of cohesion and mutual trust among residents with shared expectations for intervening in support of neighborhood social control', has the potential to modify rates of violence in some neighbourhoods (Sampson 2013:127). Using survey methods and ecometric modelling collective efficacy has been found to be a predictor of violence in North American, Western European, and Australian cities (Morenoff et al 2001;Sampson et al 2002;Mazerolle et al 2010;Sampson 2013), but weakly related to violent crime rates in London (Sutherland et al 2013) and with no apparent association to violence in Latin American cities.…”
Section: Introductionmentioning
confidence: 99%
“…Our data do not contain measures of the time participants have lived at their present address, and though we have utilized home ownership as a proxy for this measure, it is still possible that household attachment, which has previously been found to be strongly related to collective efficacy (Mazerolle et al, 2010;Sampson et al, 1997), may further help to explain our results.…”
Section: Limitationsmentioning
confidence: 99%
“…Ejemplo de esto son los trabajos de Robert Sampson ya citados, así como los de Shaw & McKay (1942), Cohen & Felson (1979), Bursik (1988), y Mazerolle et al (2010). Las diferencias con los contextos latinoamericanos son importantes y se expresan, por ejemplo, en la composición demográfi ca, en los menores niveles de desarrollo económico que implican una fuerte presencia de la economía informal y en la menor capacidad estatal para ejecutar planes y programas que reduzcan el delito, entre otros factores.…”
Section: Aproximaciones Conceptuales a La Violencia Urbana Desde Amérunclassified